2022
DOI: 10.1097/pra.0000000000000629
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of Scrupulosity Presenting as Catatonia in a Patient With Both OCD and OCPD

Abstract: We present the case of a woman in her 40s with a history of hypothyroidism, a differential diagnosis of major depressive disorder with psychotic features versus bipolar I disorder, catatonia, and anorexia nervosa. The patient was admitted to the hospital for poor oral intake, mutism, and social withdrawal. Administration of lorazepam successfully treated these presenting symptoms. However, on subsequent days, she was found to be reading the Bible almost constantly during waking hours, at the expense of engagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…To our knowledge, only fourteen case reports have been published concerning catatonia with OCD manifestation [4,8,9,[11][12][13][14][15][16][17][18][19][20], among which only four articles have shown ECT efficacy for recurrent catatonia [9,13,15,17]. A study by D'Urso et al showed successful treatment of catatonia and OCD, whereas Duarte-Batista et al in their study depicted transient improvement of catatonia, eventually requiring deep brain stimulation [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only fourteen case reports have been published concerning catatonia with OCD manifestation [4,8,9,[11][12][13][14][15][16][17][18][19][20], among which only four articles have shown ECT efficacy for recurrent catatonia [9,13,15,17]. A study by D'Urso et al showed successful treatment of catatonia and OCD, whereas Duarte-Batista et al in their study depicted transient improvement of catatonia, eventually requiring deep brain stimulation [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only fourteen case reports have been published concerning catatonia with OCD manifestation (Blacker, 1966;Duarte-Batista et al, 2020;D'Urso et al, 2012;Elia et al, 2005;Eryılmaz et al, 2014;Fontenelle et al, 2007;Hermesh et al, 1989;Jagadheesan et al, 2002;Jaimes-Albornoz et al, 2021;Makhinson et al, 2012;Mukai et al, 2011;Nikjoo et al, 2022;SACHDEVA et al, 2015), among which only four articles have shown ECT efficacy for recurrent catatonia (D'Urso et al, 2012;Eryılmaz et al, 2014;Jagadheesan et al, 2002;Makhinson et al, 2012) In our study, we present effective management of recurrent catatonia using ECT. However, despite the use of antidepressants and ERP therapy, OCD was not successfully treated.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only fourteen case reports have been published concerning catatonia with OCD manifestation (Blacker, 1966;Duarte-Batista et al, 2020;D'Urso et al, 2012;Elia et al, 2005;Eryılmaz et al, 2014;Fontenelle et al, 2007;Hermesh et al, 1989;Jagadheesan et al, 2002;Jaimes-Albornoz et al, 2021;Makhinson et al, 2012;Mukai et al, 2011;Nikjoo et al, 2022;SACHDEVA et al, 2015), among which only four articles have shown ECT efficacy for recurrent catatonia (D'Urso et al, 2012;Eryılmaz et al, 2014;Jagadheesan et al, 2002;Makhinson et al, 2012). A study by D'Urso et al showed successful treatment of catatonia and OCD whereas, Duarte-Batista et al in their study depicted transient improvement of catatonia, eventually requiring Deep Brain Stimulation (Duarte-Batista et al, 2020;D'Urso et al, 2012).…”
Section: Discussionmentioning
confidence: 99%